2007
DOI: 10.1074/jbc.m705429200
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Targeting of Ribosomes and Their Release Require Distinct and Separable Functions of FtsY

Abstract: The mechanism underlying the interaction of the Escherichia coli signal recognition particle (SRP) receptor FtsY with the cytoplasmic membrane is not fully understood. We investigated this issue by utilizing active (NG؉1) and inactive (NG) mutants of FtsY. In solution, the mutants comparably bind and hydrolyze nucleotides and associate with SRP. In contrast, a major difference was observed in the cellular distribution of NG and NG؉1. Unlike NG؉1, which distributes almost as the wild-type receptor, the inactive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
35
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 36 publications
8
35
0
Order By: Relevance
“…2A, green residues (40 -42)). Importantly, one phenylalanine in E. coli FtsY and two phenylalanines in cpFtsY preceding this motif play critical roles in inducing helix formation in this motif and are hence required for membrane binding of these receptors (40,42,48). Consistent with these results, we found that truncation of the N-terminal residues of cpFtsY (to yield cpFtsY-NG) abolished the PG-induced stimulation of GTPase assembly (Fig.…”
Section: Anionic Phospholipids Stimulate Cpsrp54⅐cpftsy Complexsupporting
confidence: 79%
“…2A, green residues (40 -42)). Importantly, one phenylalanine in E. coli FtsY and two phenylalanines in cpFtsY preceding this motif play critical roles in inducing helix formation in this motif and are hence required for membrane binding of these receptors (40,42,48). Consistent with these results, we found that truncation of the N-terminal residues of cpFtsY (to yield cpFtsY-NG) abolished the PG-induced stimulation of GTPase assembly (Fig.…”
Section: Anionic Phospholipids Stimulate Cpsrp54⅐cpftsy Complexsupporting
confidence: 79%
“…Only FtsY variants that contain at least a minimal MTS are functional in vivo and can be activated in GTP hydrolysis upon SRP interaction (13). In the crystal structure of the SRP-FtsY GTPase heterodimer, ␣N1 of the N domain is absent in both proteins (33,34).…”
Section: Mts Does Not Respond To Nucleotide-induced Conformational Chmentioning
confidence: 99%
“…However, the A domain is not essential in Escherichia coli as a truncation variant (termed NGϩ1) is functional in vivo (11). It was shown that the FtsY GTPase is activated by anionic phospholipids (9) and that the membrane interaction of FtsY is crucial for the release of RNCs from the SRP-FtsY complex (12,13), which was confirmed recently (14). Membrane interaction of E. coli FtsY depends on a conserved motif at the N terminus of the N domain, referred to as membrane-targeting sequence (MTS) (15).…”
mentioning
confidence: 99%
“…Constructs were labeled with ratios of labeled and unlabeled Met such that equal 35 35 S signal from a given protein band as analyzed by SDS-PAGE and phosphorimaging. Equimolar amounts of proteins were added to each experiment (supplemental Fig.…”
Section: Methodsmentioning
confidence: 99%